(untitled) (Bangladesh Journal of Urology, 2023)
Background: Despite the fact that shock wave lithotripsy (SWL) is a non-invasive, secure, and efficient way to treat ureteral stones, the overall stone-free rate (SFR) varies significantly depending on the location and size of the stone. Objective: To determine whether the performance of shock wave lithotripsy can be predicted using stone attenuation and skin-to-stone distance on computed tomography. Methodology: This prospective observational study was conducted in the Department of Urology at the National Institute of Kidney Diseases and Urology (NIKDU), Dhaka. Following ethical approval from NIKDU, 100 patients with ureteral stones were chosen for this study. A detailed history of these patients, as well as their drug and dietary histories, were recorded on a data collection form. Each patient had a CT scan to determine stone attenuation and skin-to-stone distance. The stone clearance rate after SWL was compared with stone attenuation and skin-to-stone distance. The Statistical Package for Social Sciences (SPSS) version 12.0 was used to analyse the data. Result: There were 66 males and 34 females among the 100 study participants. The mean age of the study subjects was 48.54 ± 7.93 years. The success of SWL was significantly higher among normal-weight patients. Failure in SWL was 15%. The mean stone-to-skin distance was 9.33 ± 2.61 cm and 12.50 ± 3.00 cm in successful and failed SWL respectively. In both successful and failed SWL, the mean stone attenuation was 790.94 ±144.72 HU and 1164.67 ± 222.67 HU, respectively. The mean volume of stone was 1302.71 ± 181.51 cm3 and 1853.33 ± 270.23 cm3 in successful and failed SWL respectively. Sensitivity, specificity, PPV, and NPV were 80.0%, 67.1%, 70.8%, and 77.0% respectively, of stone-to-skin distance in the prediction of successful SWL at a cut-off point <10.25. Sensitivity, specificity, PPV, and NPV were 86.7%, 94.1%, 93.6%, and 87.6% respectively, of stone attenuation in the prediction of successful SWL at a cut-off point <1045 HU. Conclusion: Stone attenuation and stone to skin distance are a good predictor of successful SWL. Bangladesh J. Urol. 2023; 26(1): 9-13